Analysis of an Instrumented Charpy Impact Using Power Spectrum Density - Ali, Mohd Basri (Trans Tech Publications, Switzerland, 2011)
Dynamic fracture properties of most engineering materials are evaluated using Charpy test. The dynamic responses of the standard Charpy impact machine are experimentally studied using the relevant data acquisition system in order to obtain the impact response. For this reason, strain gauges were connected to the data acquisition set and it was then attached to the striker for the signal collection. The numerical analysis by mean of the finite element method has been used to obtain the findings. The standard Charpy modelling using the aluminium 6061 material was used in order to obtain strain responses on the striker during the impact simulation. A standard Charpy specimen aluminium 6061 was used for the experimental impact testing. A power spectrum density (PSD) approach is then used to convert a signal from the time domain to the frequency domain using the fast Fourier transform (FFT) method. Related parameters on strain signals, power spectrum density (PSD), comparison between experiment and finite element analysis, and the relationship between all the parameters were finally correlated and discussed. It was found that the finite element results are validated to show simulated time histories and its PSD compared with experimental work.